Utilization of local food ingredients to prevent stunting in Menampu, Gumukmas, Jember - Janur Putri Wayanshakty (Universitas Pendidikan Indonesia, 2025)
Stunting is one of the child health problems in the form of child growth and development disorders. The 2025 Jember Regency data portal indicates that Menampu Village, Gumukmas District, is among the 10 areas with the highest stunting prevalence in Jember. To address stunting, it is necessary to optimize the use of Posyandu's resources in Jember's abundant local food sources. This series of community service activities began with a location survey. The target participants of the activity were Posyandu cadres for toddlers in Menampu Village, Gumukmas District, Jember Regency. The community service activity was held in the Menampu Village Hall with 15 participants. The method used in this community service was to provide knowledge and practice in training sessions. The success indicators of the training activity were the increase in scores from the pre-test to the post-test. The results of the training activity were evident in the increase in participants' knowledge about local food nutrition, food safety, and reading labels on packaging. Abstrak Stunting menjadi salah satu masalah kesehatan anak berupa gangguan tumbuh kembang anak. Portal data Kabupaten Jember tahun 2025 menunjukkan Desa Menampu, Kecamatan Gumukmas, termasuk dalam 10 daerah dengan prevalensi stunting tertinggi di Jember. Dalam mengatasi masalah stunting ini, maka perlu mengoptimalkan kinerja Posyandu dalam pemanfaatan sumber pangan lokal Jember yang cukup melimpah. Rangkaian kegiatan pengabdian ini diawali dengan survey lokasi. Target peserta kegiatan adalah kader Posyandu balita di Desa Menampu, Kecamatan Gumukmas, Kabupaten Jember. Kegiatan pengabdian dilaksanakan di aula Desa Menampu dengan jumlah peserta 15 orang. Metode yang digunakan dalam pengabdian masyarakat ini yaitu dengan memberikan pengetahuan dan praktik dalam sesi pelatihan. Indikator keberhasilan kegiatan pelatihan adalah peningkatan skor dari pre-test ke post-test. Hasil dari kegiatan pelatihan terlihat dari meningkatnya pengetahuan peserta tentang nutrisi makanan lokal, keamanan bahan pangan, dan pembacaan label dalam kemasan. Kata Kunci: bahan pangan lokal; gizi; stunting